Among the Senior Advisors of the Modern Assyrian kingdom 911-612 BC : The Function of the Lord rab q as a Model - عادل أبراهيم الطائي, ابتهال; حميد قاسم, فاتن (Journal of College of Education, 2021)
The Assyrians were able to establish a vast Empire that was able to Dominate most of the Ancient Near East regions with their various capabilities, As well as the Central Administration that gets to know the king about the most accurate and most dangerous details that occur in his regions and provinces, and as a result, many Administrative Positions and Functions Emerged that It included senior employees, advisors, and junior employees, so that the Assyrians had a large army of skilled and competent administrators who had different tasks, each according to his job, and based on the foregoing, our study came in two axes preceded by AHistorical introduction on the development of management in the modern Assyrian Era The First Axis: Dealt with the Activities and Tasks of rab ½q in the texts of the first Assyrian kingdom. As for the Second Axis: it was Devoted to talking about his Activities and tasks in the texts of the second Assyrian kingdom. I have also A attached two Appendices to the Search, the First is a list of the names of those who held this Position, while the Second is a map showing the boycott of rab ½q
Keywords: Assyrian Empire , rab q , Nairi